ZBYCIE RZECZY RUCHOMEJ OBCIĄŻONEJ ZASTAWEM SKARBOWYM (ZAGADNIENIA WYBRANE) - Grzegorz Jędrejek (Zeszyty Prawnicze)
Alienation of a Movable Asset Encumbered with Tax Lien Summary The article deals with selected problems referring to executive proceedings in administration in case of alienation of a movable asset encumbered with tax lien. A tax lien is a lien imposed in order to secure public imposts on movables assets or property rights. According to the author, legal proceedings are acceptable in order to conclude whether a purchaser of a movable asset encumbered with a tax lien should abolish enforcement of administrative decision. The basis for execution is not an executory entitlement in the analyzed administrative case, but an appropriate provision of statutory law, which is the article 848 of Civil Procedure Rules, used by way of analogy.